THE IMPLEMENTATION OF PROJECT BASED LEARNING TO IMPROVE STUDENTS RESPONSIBILITY IN SOCIAL STUDIES LEARNING - Sari, Novita (Universitas Pendidikan Indonesia, 2018)
This research was motivated by the results of preliminary research on social studies learning activities conducted by one of teachers in Al Musyawarah Lembang MTs which indicated that the implementation of project based learning (PBL) model could increase the responsibility of students in social studies learning. The PBL model needed to be developed by teachers during the process of learning activities so that students have a sense of responsibility towards themselves, society, environment, and nation that students are able to bear the risk of decisions and have the provision to face challenges in future. The method used in this study was a descriptive method and the participants was social studies teachers and students of class VIII-AB MTs Al Musyawarah Lembang, consisted of 42 students divided into 21 female students and 21 male students. Data collection techniques used were observation, interviews and documentation. The results of the study showed that the implementation of Â PBL model could enhance students' sense of responsibility. This could be supported by observational data on students' sense of responsibility in participating learning activities in class and completing project assignments that could be developed through PBL learning models that showed the increase of responsibility such as diligent, active and enthusiastic in participating learning process.Keywords: Project Based Learning Model (PBL), Responsibility.